Creating an Article Repository using LibSys: A Case Study of JRD Tata Memorial Library - Chudamani, K.S.; Nagarathna, H.C. (DESIDOC Journal of Library & Information Technology, 2010)
Article Repositories are an integral part of present day digital libraries permitting global access to the scholarly publications. An article repository system can be created using LibSys software, and help LibSys users collaboratively create a federated search engine to share resources among themselves. This article highlights the system used by the JRD Tata Memorial library of Indian Institute of Science, Bengaluru for providing open access to articles published by its faculty. http://dx.doi.org/10.14429/djlit.29.267